Evaluation of the Acceptance of the Developer Registration System Using the TAM Framework with the Perspective of Housing Developers and Associations in Indonesia - Wirani, Yekti; Nadira, Elsa; Romadhon, M. Syaiful (Universitas Nusantara PGRI Kediri, 2021)
The Developer Registration System (SIRENG), owned by the Ministry of Public Works and Public Housing of the Republic of Indonesia, aims to provide supervision on the quality of houses built by housing developers. Based on the interviews with the association manager PERWIRANUSA, the completeness and suitability of the information in SIRENG are still limited. It does not meet SIRENG development benefits, guaranteeing that registered developers in SIRENG are experienced and trusted. This study aims to provide recommendations for managers of SIRENG to improve the system through evaluation of acceptance of SIRENG with the association and housing developer's perspective. This study uses the Technology Acceptance Model (TAM) framework and utilizes PLS techniques to analyze respondents' data. This study used a mixed-method. This study's results are Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Actual Usage (AU) variables that influence the acceptance of SIRENG.